Judicial Activism in Regulating ‘Human Rights Violations’ by Police Authorities in India - Sandeepa Bhat, B. (Kathmandu School of Law Review, 2017)
The human right violations in police’s actions (or inaction) are in the headlines, quite often in India. The fundamental freedoms guaranteedunder the Indian Constitution are often ignored during the course of such police actions, which the Judiciary in India has tried to regulate in many cases. The Supreme Court of India has laid down norms for many areas including custodial death, inhuman treatment in prisons, continued detentions in the prison after the completion of a term of imprisonment, fake encounters, unwarranted breach of the right to privacy of individuals and registering of fraudulent cases. Despite the continued efforts of the Indian Judiciary, the incidents of human right violations by the police have not abated due to two main reasons: a) the strong political influence of the police and b) theignorance of the public, who still fear the police more than anyone else. This paper addresses the topic at hand in three parts. In the first part, the paper analyses the trendsetting judicial verdicts against the violation of human rights by police in India, especially in light of the Constitutional provisions. The second part addresses the problems that are still faced despite the judicial activism in the field and elaborates on the reasons for the continuation of problems. The final part of the paper addresses thesteps that can be taken for strengthening the police reforms to prevent human right violations. It also looks into the need for necessary responses from other stakeholders in the field.